Static analysis 18th international symposium, SAS 2011, Venice, Italy, September 14-16, 2011 : proceedings - Yahav, Eran. (Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the 18th International Symposium on Static Analysis, SAS 2011, held in Venice, Italy, in September 2011. The 22 revised full papers were selected from 67 submissions. Also included in this volume are the abstracts of the invited talks that were given at the symposium by renowned experts in the field. The papers address all aspects of static analysis, including abstract domains, abstract interpretation, abstract testing, data flow analysis, bug detection, program transformation, program verification, security analysis and type checking.
Keywords: Computer programming -- Congresses; Programming languages (Electronic computers) -- Congresses; Electronic books